1995
DOI: 10.1210/endo.136.11.7588218
|View full text |Cite
|
Sign up to set email alerts
|

Desensitization of gonadotropin-releasing hormone action in the gonadotrope-derived alpha T3-1 cell line.

Abstract: Sustained exposure of gonadotropes to GnRH causes a pronounced desensitization of GnRH-stimulated gonadotropin release, but the mechanisms involved are poorly understood. Recent studies have suggested, however, that GnRH-stimulated phosphoinositidase C (PIC) activity does not undergo rapid ( < 5 min) homologous desensitization in alpha T3-1 cells, and we have, therefore, used this cell line to address the question of whether desensitization occurs distal to PIC activity and/or in an intermediate time frame. We… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
31
0
1

Year Published

1999
1999
2017
2017

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 60 publications
(33 citation statements)
references
References 0 publications
1
31
0
1
Order By: Relevance
“…The recent discovery that mammalian GnRH receptors do not show rapid homologous desensitization (3)(4)(5)(6)(7)(8) reveals that desensitization of GnRH-stimulated gonadotropin secretion must reflect changes distal to the receptor, as implied by earlier work showing that GnRH receptor regulation does not explain desensitization of gonadotropin secretion (5). Our work has revealed that pretreatment of ␣T3-1 cells with GnRH causes a pronounced desensitization of GnRHstimulated mobilization of Ca 2ϩ from intracellular stores (4, 5), which is of particular interest in the light of the established importance of Ca 2ϩ mobilization in mediation of GnRH-stimulated gonadotropin secretion.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The recent discovery that mammalian GnRH receptors do not show rapid homologous desensitization (3)(4)(5)(6)(7)(8) reveals that desensitization of GnRH-stimulated gonadotropin secretion must reflect changes distal to the receptor, as implied by earlier work showing that GnRH receptor regulation does not explain desensitization of gonadotropin secretion (5). Our work has revealed that pretreatment of ␣T3-1 cells with GnRH causes a pronounced desensitization of GnRHstimulated mobilization of Ca 2ϩ from intracellular stores (4, 5), which is of particular interest in the light of the established importance of Ca 2ϩ mobilization in mediation of GnRH-stimulated gonadotropin secretion.…”
Section: Discussionmentioning
confidence: 99%
“…Determination of Ins (1,4,5) Ϫ5 M unlabeled Ins(1,4,5)P 3 . The incubations were terminated by centrifugation and removal of supernatants by aspiration.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…This is true of the GnRH-R expressed either as an endogenous protein in an immortalized mouse pituitary cell line (␣T3-1) or as a recombinant protein in a number of cell types (2)(3)(4)(5). Furthermore, we have recently demonstrated that, although GnRH-Rs of ␣T3-1 cells are not acutely regulated, muscarinic M 3 receptors co-expressed as recombinant proteins in these cells are rapidly desensitized (6).…”
mentioning
confidence: 99%